Subcutaneous cysticercosis mimicking tenosynovitis: a rare case with radiological revelation - Soni, Jinal R.; Chaturvedi, Ved P. (International Journal of Research in Medical Sciences, 2023)
Subcutaneous cysticercosis is a rare manifestation of cysticercosis, caused by the larval stage of Taenia solium. It presents as a swelling or a palpable cystic mass. We describe a 43-year-old female who presented with subcutaneous swelling over her right hand, gradually increasing in size over ten days. Initially, tenosynovitis was suspected clinically. However, an ultrasound of the hand revealed a well-defined, cystic lesion with eccentric echogenic foci and peripheral oedema suggestive of cysticercosis. She was treated with oral albendazole, leading to significant improvement. This case report emphasizes the importance of considering parasitic infections as a potential cause of subcutaneous swelling. It also highlights the significance of utilizing diagnostic imaging for definitive diagnosis and timely treatment.